Seneca, Corneille, and the Ghost of Jesuit Classicism - Boparai, Jaspreet Singh (Journal of Jesuit studies, 2024)
The precise effects of Jesuit education can be difficult to discern in a given writer or artist. Little is known about Pierre Corneille’s (1605–84) humanist formation at the Jesuit college in Rouen; like his philosophical orientation, its nature must be extrapolated from scanty, equivocal evidence. This article traces Corneille’s reception of Seneca (c.4 bce–65 ce) in his early tragedy Médée and his heroic drama Cinna in an attempt to come to grips with his idiosyncratic classicism, which diverges considerably from contemporary Aristotelianism. Corneille is a practical man of the theatre and focuses less on Aristotle than on Seneca’s philosophical prose, as well as his tragedies. By the time he comes to compose Rodogune, Corneille has absorbed Seneca so completely that it seems almost impossible to articulate precisely how his work is “Senecan,” except to point to Seneca’s shadow. Perhaps Jesuit classicism is easier to study in a less idiosyncratic writer like Thomas Corneille (1625–1709)?